Implementasi Algoritma Rabin Karp Pada Aplikasi Muroja’ah Hafalan Al-Qur’an Menggunakan Google Speech API Berbasis Android - Muhammad Khoir Al Alim Manurung; Samsudin Samsudin; Ali Ikhwan (UNIVERSITAS RAHARJA, 2022)
The muroja'ah application in Al-Qur'an memorizing is an android-based application that is used to help memorizers of the Al-Qur’an in doing muroja'ah memorization. The application is built using Speech Recognition in Artificial Intelligence (AI) technology by implementing the Google Speech API and the Rabin Karp Algorithm to convert the user's speech into a string which is then compared with the correct verse string. As for data collection methods, the author uses qualitative research methods, by conducting observations, interviews, and literature research. The application that was built successfully implemented the Google Speech API feature along with the Rabin Karp Algorithm with the output displaying information about the correct status or not along with the percentage accuracy of the similarity between the correct verse data and the voice spoken by the user.